Peculiarities of acute phase response in various types of uterine appendages inflammation - S. V. Shramko; N. V. Zorina; L. G. Bazhenova; R. M. Zorina (Бюллетень сибирской медицины)
Concentrations of some acute phase proteins (alpha-1-antitrypsin or AT; alpha-2-macroglobulin or MG; pregnancy associated alpha-2-glycoprotein or PAG) and lactoferrin (Lf) were studied in blood serum of 82 women with various types of uterine append-ages inflammation. The data obtained have been compared with conventional and commonly used laboratory indices of inflammato-ry response such as fibrinogen (Fbg) and leukocyte intoxication index. Our findings confirmed significant role of macroglobulin family proteins in the development of acute phase inflammation. Associated tendencies in changes of acute phase proteins concen-trations in various types of uterine appendages inflammation have been identified and recommended to be employed in clinical prac-tice for making differential diagnosis and for selection of optimal therapeutic approach.